(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Use of face masks and respirators are significant in preventing the transmission of coronavirus disease 2019 (COVID-19) via respiratory droplets or aerosols. The development of face masks and respirators have been focused on the modification using nanoparticles (NPs) to obtain biocidal activities. The incorporation of NPs can also increase the hydrophobicity of the material that assists the repelling of virus carrying droplets or aerosols. Nevertheless, the common cost of gaining those benefits is breathability. Previous studies have reported on the discomforts of wearing a face mask or respirator, one of which is stems from breathing difficulty. At the time of pandemic, maintaining the comfort wearing of face masks or respirators is even more crucial. Thus, this review article is important to keep the breathability aspect gaining a spotlight in the development of NPs-modified face masks or respirators. Herein, we discuss the relationship between the addition of NPs with breathability of the material. In the beginning of discussion, types of protective respiratory equipments, and biocidal activities of the modified fabrics are discussed. Strategies in maintaining the air permeability for long duration use and self-cleansing feature are also discussed.